2017
DOI: 10.1080/20009666.2017.1361293
|View full text |Cite
|
Sign up to set email alerts
|

Use of dark chocolate for diabetic patients: a review of the literature and current evidence

Abstract: Dietary changes are a major lifestyle factor that can influence the progression of chronic diseases such as diabetes. Recently, flavanols, a subgroup of plant-derived phytochemicals called flavonoids, have gained increasing attention, due to studies showing an inverse correlation between dietary intake of flavanols and incidence of diabetes. Flavanoids in the cocoa plant may ameliorate insulin resistance by improving endothelial function, altering glucose metabolism, and reducing oxidative stress. Oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Altogether, our results indicate that cocoa intake prevented increased blood pressure and aortic stiffness in ZDF diabetic animals. This vascular protective effect of cocoa has also been demonstrated in similar experimental models of cardiovascular risk such as hypertension and supported several small interventional studies suggesting that cocoa may also have therapeutic potential in preventing cardiovascular complications in diabetic patients …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Altogether, our results indicate that cocoa intake prevented increased blood pressure and aortic stiffness in ZDF diabetic animals. This vascular protective effect of cocoa has also been demonstrated in similar experimental models of cardiovascular risk such as hypertension and supported several small interventional studies suggesting that cocoa may also have therapeutic potential in preventing cardiovascular complications in diabetic patients …”
Section: Resultssupporting
confidence: 73%
“…Altogether, these interesting novel findings reveal the beneficial effect of cocoa intake in improving vascular structural changes and remodeling in ZDF rats. Although, interventional studies evaluating the consumption of cocoa products in T2D patients are very limited, results from some small human studies have also showed a protective effect of cocoa intake on vascular function . Therefore, additional clinical trials in individuals with diabetes are needed in order to clarify the potential of cocoa to reduce the risk of vascular complications in diabetics.…”
Section: Resultsmentioning
confidence: 99%
“…Combined endocardial–epicardial VT ablation has had significant short- and long-term success rates compared to endocardial VT ablation alone [22,49]. VT recurrence following VT ablation could be explained by the patchy nature of ARVC; hence, development of new arrhythmic foci is not infrequent [32,50,51]. Therefore, RFA is currently not recommended as stand-alone therapy or as an alternative to ICD for ARVC patients due the progressive nature of ARVC (class III) [22].…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…The medicinal properties of dark chocolate (DC) and other foodstuffs derived from Theobroma cacao were first noted centuries ago dating back to the time of Christopher Columbus whose expeditions first brought cocoa to Europe and introduced DC into European culinary culture [1, 2]. Amelioration of fatigue, indigestion, and other gastrointestinal disorders were attributed to the potential medicinal benefits associated with regular consumption of DC [1].…”
Section: Introductionmentioning
confidence: 99%